Health-related quality of life following percutaneous coronary intervention during the COVID-19 pandemic - Dawson, L.P.; Dinh, D.T.; Stub, D.; Ahern, S.; Bloom, J.E.; Duffy, S.J.; Lefkovits, J.; Brennan, A.; Reid, Christopher; Oqueli, E. (SPRINGER, 2022)
Purpose: During the COVID-19 pandemic, widespread public health measures were implemented to control community transmission. The association between these measures and health-related quality of life (HRQOL) among patients following percutaneous coronary intervention has not been studied. Methods: We included consecutive patients undergoing percutaneous coronary intervention (PCI) in the state-wide Victorian Cardiac Outcomes Registry between 1/3/2020 and 30/9/2020 (COVID-19 period; n = 5024), with a historical control group from the identical period one year prior (control period; n = 5041). HRQOL assessment was performed via telephone follow-up 30 days following PCI using the 3-level EQ-5D questionnaire and Australian-specific index values. Results: Baseline characteristics were similar between groups, but during the COVID-19 period indication for PCI was more common for acute coronary syndromes. No patients undergoing PCI were infected with COVID-19 at the time of their procedure. EQ-5D visual analogue score (VAS), index score, and individual components were higher at 30 days following PCI during the COVID-19 period (all P < 0.01). In multivariable analysis, the COVID-19 period was independently associated with higher VAS and index scores. No differences were observed between regions or stage of restrictions in categorical analysis. Similarly, in subgroup analysis, no significant interactions were observed. Conclusion: Measures of HRQOL following PCI were higher during the COVID-19 pandemic compared to the previous year. These data suggest that challenging community circumstances may not always be associated with poor patient quality of life.